Mierniki koncentracji przestrzennej w analizie aktywności ekonomicznej ludności w Polsce - Antczak, Elżbieta; Żółtaszek, Agata (Selected Indexes of Spatial Concentration in the Analysis of Human Economic Activity in Poland, 2009)
The aim of this paper is to present and apply selected spatial concentration indexes, such as: Location Quotient, spatial Gini, Hirschman-Herfindahl. These indicators are used to measure inequality and concentration of the level of employment in the agricultural sector in Polish voivodships. The comparison analysis was also carried out. The research concerns years 2005-2008. Finally, the study leads to the verification of concentration of this phenomenon considering its heterogeneity and time-changing data. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 341-348